A Case of Cutaneous T-Cell Lymphoma with Nodular Skin Lesions, Third Nerve Palsy and Peripheral Vascular Disease: Can It Be a Case of Angiocentric Lymphoma? (BIRDEM Medical Journal, 2016)
Angiocentric lymphoma is a subtype of cutaneous T-cell lymphoma, characterized by occlusion of vessels by lymphoid infiltrate. Here, we report a case of biopsy confirmed cutaneous T-cell lymphoma who presented with third cranial nerve palsy, peripheral vascular disease and nodular skin lesions in the right thigh. All these findings of this case can be explained by mechanism of vascular infiltration and tissue destruction in angiocentric lymphoma which is a rare disorder.Birdem Med J 2016; 6(1): 40-42